Mass spectroscopic analysis of phosphatidylinositol synthesis using 6-deuteriated-myo-inositol: comparison of the molecular specificities and acyl remodelling mechanisms in mouse tissues and cultured cells. (26th October 2004) - Postle, A.D.; Dombrowsky, H.; Clarke, H.; Pynn, C.J.; Koster, G.; Hunt, A.N.
Abstract : Mammalian cell PtdIns (phosphatidylinositol) in vivo is enriched in the sn -1-stearoyl 2-arachidonoyl species, the physiological precursor of phosphatidylinositol 4, 5-bisphosphate. Mechanisms regulating this specificity are unclear but are typically lost for cells in culture. We used ESI-MS (tandem electrospray ionization-mass spectrometry) to determine the molecular species of PtdIns synthesized by mouse tissues in vivo compared with cultured cells in vitro . After incorporation of deuteriated myo-d 6 -inositol over 3 h, endogenous and newly synthesized PtdIns and lysoPtdIns species were quantified from precursor scans of m / z 241 − and m / z 247 − respectively. PtdIns was synthesized as a wide range of species irrespective of the final membrane composition. Analyses of isotope enrichments argued against acyl remodelling as the major regulatory mechanism: composition of the lysoPtdIns pool under all conditions reflected that of either endogenous or newly synthesized PtdIns and was always at equilibrium. The kinetics of PtdIns synthesis, together with the prolonged time scale required for achieving final equilibrium compositions suggest that selective transport between membranes and/or hydrolysis of selected molecular species are the most probable mechanisms regulating compositions of PtdIns and, ultimately, phosphatidylinositol 4, 5-bisphosphate.